ANALISIS Analisis Makna dan Simbol dalam Pernikahan Adat Nias - Wahyu Zebua, Angelia Febryanti (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the meaning and symbols in Nias traditional weddings. The method used in this research is descriptive qualitative. This research process uses Roland Barthes' theory. The data used in this research are dialogues used in wedding ceremonies, words, sentences, texts and images in the field about the meaning and symbols of traditional Nias weddings and the book Fondrakö published by the Gunungsitoli City Tourism and Culture Office 2019, a book by Laoli ( 1985) Research Team: Nias Regional Wedding Customs and Ceremonies (published by the North Sumatra Regional Library) and also an interview with Mr. Ama Cece, a Nias humanist in the city of Gunungsitoli. The results of this research are presented in the form of an analysis of the symbols and meanings used in traditional Nias wedding ceremonies.